Faktor Penyebab Cost Overrun Pada Proyek Konstruksi di Kota Surabaya - Cornelia Larisa Rianti (Jurnal Vokasi Teknik Sipil, 2025)
Abstract The construction projects in the city of Surabaya are currently experiencing significant growth, both in terms of physical scale and costs. However, in practice, problems often arise when a construction project faces cost overruns during its execution phase. Several factors influence this, including internal and external factors related to the construction work itself. Therefore, each factor needs to be carefully considered or consistently accounted for from the preliminary estimation stage, to anticipate or avoid cost overruns in construction projects. To find solutions to the issue of cost overruns, the value of cost overruns can be minimized in future projects. Furthermore, it is important to identify the main factors causing cost overruns, which can be analyzed from each phase of design, execution, and monitoring of costs and project duration. The factors that trigger cost overruns in construction projects in Surabaya, from the contractor's perspective, include materials, labor, project duration, and cost evaluation. Among these factors, cost evaluation is the primary factor influencing the occurrence of cost overruns in Surabaya. Keywords: Cost, Cost Overrun, Cost Evalutation..